Consumer Actual Purchases on Premium Healthy Beverages: A Study of New Technology Cold-Pressed Fruit Processing - Utami, Hesty Nurul; Putri, Rifa Fajriani; Wiyono, Sulistyodewi Nur; Nurseto, Hardian Eko; Noor, Trisna Insan (Fakultas Pertanian Universitas Padjadjaran, 2024)
The paper focuses on the factors influencing consumers' actual purchase decisions for healthy products using new technology to produce fresh product-based beverages. Cold-pressed juice is a premium beverage made from fresh produce with a new technology-based process that can produce high nutrition as an alternative for the consumer's diet. The research examines the relationship between price, promotion, and product quality on consumers' purchase decisions on beverages with premium categories. A survey was conducted among 50 respondents of urban consumers who have experience buying premium healthy beverages of the brand XYZ in two outlets in Jakarta. The mean value and rank Spearman correlation analysis revealed that product quality, promotion, and price, in a particular order, were the best factors evaluated by customers, and these factors significantly correlate with purchase decisions. Product quality is the most considered by customers; however, only product quality affects consumer purchase decisions among the three factors. The findings may help processed fresh produce beverage processors and outlet owners understand the factors affecting customer purchase decisions to buy such premium fresh produce beverages. It also enables them to make better decisions in emerging technology-based beverage production for fresh produce commodities and food retail development, including supporting consumer diet choices.